A Report on a Family with TMTC3-Related Syndrome and Review - Sayeeda Hana; Deepak karthik; Jingxuan Shan; Stephany El Hayek; Lotfi Chouchane; André Megarbane (Case Reports in Medicine)
Recessive mutations in the TMTC3 gene have been reported in thirteen patients to date exhibiting development delay, intellectual disability (ID), seizures, and muscular hypotonia, accompanied occasionally by neuronal migration defects expressed as either cobblestone lissencephaly or periventricular hypertopia. Here, we report a new case of a TMTC3-related syndrome in a Lebanese family with two affected siblings showing severe psychomotor retardation, intellectual disability, microcephaly, absence of speech, muscular hypotonia, and seizures. Whole exome sequencing revealed a homozygous pathogenic variant c.211 C > T (p.R71C) in the TMTC3 gene in both siblings. A review of the literature on TMTC3-related syndrome and its causal mutations is provided.